Pengaruh Profitabilitas, Makroekonomi, Firm Size Terhadap Financial Distress Dengan Nilai Perusahaan Sebagai Variabel Moderating - Heliani Heliani; Siti Elisah (Owner : Riset dan Jurnal Akuntansi, 2022)
One of the key contributors to the country's economic health is the banking industry. From 2017 to 2021, there were eight banking companies that were liquidated. So it is necessary to anticipate from the beginning so that bankruptcy does not occur. One way to see if a company is in financial distress can be done using the Altman's Z-Score method. This investigation was carried out with the intention of measuring and knowing the extent to which profitability, macroeconomic, and firm size ratios are proxied by Return On Assets (ROA), inflation, and total assets to financial distress using the Altman's Z-Score method through a moderating variable in the form of firm value proxied by PBV. This is a quantitative study that relies on secondary data gathered through a literature review. The population of this study is the whole banking industry in Indonesia, with a total sample of 23 enterprises acquired using the purposive sampling approach. This study employs panel data using the Moderated Regression Analysis (MRA) approach, which is carried out using Econometric Views (Eviews) version 10. According to the findings of this study, profitability had a favorable influence on financial distress, but macroeconomics, business size, and firm value had no effect. Meanwhile, firm value is deemed unable to moderate the independent variable on the dependent variable in this study, so it is unknown whether firm value increases or weakens the independent variable on the dependent variable.